Design and Implementation of IOT-Based Intravenous (IV) Bag Monitoring and Alert System - Gregory T. AKAU; Abel AIROBOMAN; Nathaniel DALLA (FUDMA Journal of Engineering and Technology, 2025)
Health, being a critical aspect of daily life, demands heightened attention, especially when a patient is hospitalized. In densely populated hospitals with limited nursing staff, the continuous monitoring of Intravenous (IV) fluid becomes a challenge. If the IV fluid is not properly monitored, severe consequences may arise, such as blood reflux or the entry of air bubbles into the patient's bloodstream when the fluid bottle runs dry. To address this, the project proposes the design and implementation of an IoT-based intravenous infusion monitoring and Alert System using the Huamao Communication 12 radio frequency module (HC-12) for wireless communication. The system also integrates Espressif Wi-Fi SoC ESP8266 wi-fi connectivity for real-time data transmission to the ThinkSpeak cloud platform. The hardware setup includes a load cell with an HX711 interface for continuous measurement of the IV fluid's weight, and a laser sensor positioned on the drip chamber to monitor the droplet rate. An Arduino Uno microcontroller coordinates the sensors and decision logic. When the fluid level drops below a critical threshold or the drip rate becomes abnormal, an alert is transmitted wirelessly via the RF module to a remote receiver unit (e.g., nurse’s station), where the patient's information and alert status are displayed. Additionally, the ESP8266 module uploads real-time data to the internet for remote monitoring and analytics. The performance evaluation of the prototype demonstrated a system success rate of approximately 96.8% in accurately detecting both low-fluid and abnormal drip rates. This low-cost, easily deployable system enhances patient safety by ensuring timely intervention from medical staff and is particularly suited for resource-constrained hospitals that cannot afford expensive commercial IV monitoring system.
Keywords: Intravenous (IV) monitoring, IoT-based healthcare, Arduino Uno, drip rate monitoring, ESP8266 Wi-Fi, ThingSpeak cloud, hospital automation.